FROM LOYALTY TO ADVOCACY: THE MEDIATING ROLE OF INSTITUTIONAL IDENTIFICATION ON STUDENT CITIZENSHIP BEHAVIOR IN INDONESIAN HIGHER EDUCATION - Iskandar Arifin; Mirandha Ariesca Riana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the mediating role of institutional identification between brand loyalty and Student Citizenship Behavior (SCB) in Indonesian higher education. Using a quantitative design with 350 student respondents and PLS-SEM analysis, findings reveal that brand loyalty significantly impacts institutional identification (β=0.750) and SCB (β=0.247). Crucially, institutional identification partially mediates this relationship (VAF=63.8%), effectively amplifying loyalty's impact on SCB. Validating Social Identity Theory, this study establishes institutional identification as the key "psychological bridge" transforming loyalty into voluntary extra-role behavior. Practically, higher education administrators are advised to shift focus from transactional service satisfaction to identity management strategies, fostering a narrative of "us" and symbolic pride to encourage active student advocacy.